Normal hematopoietic stem cells within the AML bone marrow have a distinct and higher ALDH activity level than co-existing leukemic stem cells. - Gerrit J Schuurhuis (Public Library of Science (PLoS), 2013)
Persistence of leukemic stem cells (LSC) after chemotherapy is thought to be responsible for relapse and prevents the curative treatment of acute myeloid leukemia (AML) patients. LSC and normal hematopoietic stem cells (HSC) share many characteristics and co-exist in the bone marrow of AML patients. For the development of successful LSC-targeted therapy, enabling eradication of LSC while sparing HSC, the identification of differences between LSC and HSC residing within the AML bone marrow is crucial. For identification of these LSC targets, as well as for AML LSC characterization, discrimination between LSC and HSC within the AML bone marrow is imperative. Here we show that normal CD34+CD38- HSC present in AML bone marrow, identified by their lack of aberrant immunophenotypic and molecular marker expression and low scatter properties, are a distinct sub-population of cells with high ALDH activity (ALDH(bright)). The ALDH(bright) compartment contains, besides normal HSC, more differentiated, normal CD34+CD38+ progenitors. Furthermore, we show that in CD34-negative AML, containing solely normal CD34+ cells, LSC are CD34- and ALDH(low). In CD34-positive AML, LSC are also ALDH(low) but can be either CD34+ or CD34-. In conclusion, although malignant AML blasts have varying ALDH activity, a common feature of all AML cases is that LSC have lower ALDH activity than the CD34+CD38- HSC that co-exist with these LSC in the AML bone marrow. Our findings form the basis for combined functionally and immunophenotypically based identification and purification of LSC and HSC within the AML bone marrow, aiming at development of highly specific anti-LSC therapy.